Taxonomic studies on Dasyproctus Lepeletier & Brullé (Hymenoptera: Crabronidae) from North Vietnam with description of two new species - Pham, Phong Huy (Zootaxa, 2022)
Seven species of Dasyproctus Lepeletier & Brullé, 1835 (Hymenoptera: Crabronidae) are recorded from North Vietnam. Of these, D. vietnamensis and D. longi are new species, and D. idrieus (Cameron) and D. pentheri Leclercq are recorded for the first time from the country. Keys to both sexes of Dasyproctus from North Vietnam based on morphological characters are given, and new distributional records are also presented.